Las tareas de aprendizaje en octavo y noveno EGB superior de la Unidad Educativa Luis Felipe Borja. - Clavijo Bohórquez, Byron Augusto (2021)
The present investigation starts from the analysis of the problems that originate in the approach of the school tasks, the fulfillment of the objectives of the learning process and its results. To determine a situational diagnosis of the students, teachers and campus authorities, around this issue, surveys and interviews were carried out, respectively with the members of the educational unit. Based on these results, the objective of making a methodological strategy guide was set, which supports the activities of teachers and serves as a consultation tool in the subjects taught at the Upper Basic level, the research has a quantitative approach and is based on the deductive method; where causes and effects are raised. In addition, it takes existing theories and relates them to the results of the research, seeking to confront the theory with the practice in order to resolve the difficulties encountered in the application of the proposal. The content of the proposal is supported by innovative methodologies, compiled from documents with scientific and theoretical validity, this information was compiled and systematized, in a strategy guide, in such a way that it is conducive to be applied in the specific environment of the Educational Unit "Luis Felipe Borja". After the socialization with experts and users, positive results were obtained, improving the indicators collected prior to carrying out this study. With these results, the main objective formulated for the application of the proposal was fulfilled, thus determining its feasibility and applicability within the institution.